Efficiency of recovery of endometrium after legal abortion at extracorporal antibiotic prophylaxis - O. A. Tikhonovskaya; O. M. Fokht; S. V. Logvinov (Бюллетень сибирской медицины, 2008)
The purpose of this study was to estimate the efficiency of preventive maintenance of postabortive complications by infusion of autogenic cefamizine-loaded blood cells and use of oral contraceptives and Polyoxidonium» Clinical estimation, ultrasonography, biopsy and immune coloring with progesterone and оestradiolum receptors in 35 women with the proposed method and 35 women with the standard method was used. It was revealed that application of the proposed method favored restoration of endometrium steroid receptors. As a result, the proposed method favors preservation of the reproductive function in women to a greater degree than the traditional method does.